PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA MATA PELAJARAN IPAS SISWA SEKOLAH DASAR - Abib Hazabi, Muhammad; Yandri Kusuma, Yanti; Sumianto; Marleni, Lusi; Syahrul Rizal, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students’ conceptual understanding in the Integrated Science and Social Studies (IPAS) subject through the application of the Contextual Teaching and Learning (CTL) model in Grade IV of UPT SDN 019 Muara Uwai. This research is a Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of the stages of planning, implementation, observation, and reflection. The research subjects were 15 students, consisting of 10 boys and 5 girls. Data collection techniques included observation, tests, and documentation, with instruments such as teacher and student activity observation sheets and conceptual understanding tests. The results showed that the application of the CTL model could improve students’ conceptual understanding. This was evident from the improvement in students’ learning outcomes in each cycle. Before the action (pre-cycle), the average score of students’ conceptual understanding was only 70, with a learning mastery of 40%. After implementing the CTL model in Cycle I, learning mastery increased to 73.3%, and in Cycle II, it rose again to 93.3%. Teacher and student activities also improved significantly, as indicated by the increasing student engagement in more meaningful and contextual learning activities. Therefore, the implementation of the Contextual Teaching and Learning (CTL) model proved effective in enhancing students’ conceptual understanding in the IPAS subject for Grade IV at UPT SDN 019 Muara Uwai. This model can serve as an alternative, creative, and innovative teaching strategy for teachers to create learning experiences that are more active, meaningful, and student-centered.